Experimental and theoretical studies of 4, 6-diamino-2-mercaptopyrimidine as a copper inhibitor in 3.5 wt% NaCl solution. Issue 18 (5th February 2016) - Cheng, Zhi; Mo, Shi; Jia, Jing; Feng, Ji; Luo, Hong Qun; Li, Nian Bing
Abstract : 4, 6-Diamino-2-mercaptopyrimidine can be adsorbed on copper surface and exhibits a high corrosion inhibition efficiency in 3.5 wt% NaCl solution. Abstract : The inhibition effect of 4, 6-diamino-2-mercaptopyrimidine (DAMP) as a copper corrosion inhibitor in 3.5 wt% NaCl solution was investigated by weight loss, electrochemical impedance spectroscopy, and potentiodynamic polarization. The inhibition efficiency increased with increasing DAMP concentration in the range of 1.0 to 2.0 mM DAMP and decreased with increasing temperature. The obtained results showed that DAMP inhibited both the anodic and cathodic currents and the maximum inhibition efficiency reached 93.2% at 2.0 mM DAMP. The inhibition performance of DAMP was confirmed by SEM and EDS. Quantum chemical calculations revealed that the DAMP molecule was adsorbed on the copper surface in a paralleled way through S and N atoms and the pyrimidine ring. Adsorption of DAMP was found to obey the Langmuir adsorption isotherm.